Age aspects of the effects of the new coronavirus infection (COVID 19) on certain biochemical blood parameters - M. M. Alimurzaeva; S. M. Izudinova; A. M. Dzhafarova; R. A. Khalilov (Медицинский вестник Юга России, 2023)
Objective: to study the effects of a new coronovirus infection on a number of standard biochemical blood parameters in patients of different ages.   Materials and methods: 514 patients of 3 age groups (group 1st — 25–35 years old, group 2nd — 36–50 years old and group 3rd — over 51 years old) with a diagnosis of community-acquired pneumonia caused by COVID-19 infection were studied. All biochemical parameters of the blood of patients were determined using an Indiko biochemical analyzer.   Results: the study of nitrogen metabolism indicators showed that in patients of all age groups, the content of total protein and urea does not undergo significant changes, however, there is an increase in the concentration of creatinine and uric acid, which is most pronounced in patients of the group 3rd. The study of the activities of AST, ALT in the blood of patients showed a significant increase in all age categories, more significant in persons of the groups 2nd and 3rd. At the same time, the activity of α-amylase, the concentration of bilirubin increase with age, and the levels of iron decrease, reaching pathological values. The content of the inflammation marker — CRP shows the most pronounced dependence on the age of patients: in patients of the group 1st, it increases by 6.9 times, in the 2nd group — by 12.3 times, in patients over 51 years old — by 17.25 once.   Conclusion: with an increase in the age of patients, the deviations of many biochemical parameters from the control levels corresponding to each group become more pronounced and reach values that deviate significantly from the reference.